2018
DOI: 10.1088/1741-2552/aaaa76
|View full text |Cite
|
Sign up to set email alerts
|

Reduced integration and improved segregation of functional brain networks in Alzheimer’s disease

Abstract: These findings may contribute to the development of EEG network-based test that could strengthen results obtained from currently-used neurophysiological tests in neurodegenerative diseases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 98 publications
3
52
2
Order By: Relevance
“…It is based on the inverse of the shortest path length, which is an indicator of the ease with which each node can reach other nodes within the network using a path that is composed of only a few edges. Hence, the global efficiency is an indicator of the degree to which a network can share information between distributed regions (Kabbara et al, 2018) Centrality. Betweenness centrality (BC) is a measure of centrality.…”
Section: Intra-brain Metricsmentioning
confidence: 99%
“…It is based on the inverse of the shortest path length, which is an indicator of the ease with which each node can reach other nodes within the network using a path that is composed of only a few edges. Hence, the global efficiency is an indicator of the degree to which a network can share information between distributed regions (Kabbara et al, 2018) Centrality. Betweenness centrality (BC) is a measure of centrality.…”
Section: Intra-brain Metricsmentioning
confidence: 99%
“…Recently, a study showed that there is no potential bias of the use of a template MRI as compared to individual MRI coregistration (Douw et al, 2018). In this context, a considerable number of EEG/MEG connectivity studies have used the template-based method due to the unavailability of native MRIs Kabbara et al, 2018;Lopez et al, 2014). However, we are aware that the use of subject-specific MRI is more recommended in clinical studies.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Electrode impedances were kept below 20 kOhm. EEG signals are frequently contaminated by several sources of artifacts, which were addressed using the same preprocessing steps as described in several previous studies dealing with EEG resting-state data (Kabbara et al, 2017;Kabbara et al, 2018;Rizkallah et al, 2018). Briefly, bad channels (signals that are either completely flat or contaminated by movement artifacts) were identified by visual inspection, complemented by the power spectral density.…”
Section: Data Acquisition and Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…To compute the dynamic functional connectivity, the steps adopted here are the same used in many previous studies Kabbara et al, 2018Kabbara et al, , 2017. First, EEG data were co-registered with a template MRI through identification of the same anatomical landmarks (left and right pre-auricular points and nasion).…”
Section: Real Datamentioning
confidence: 99%